2004
DOI: 10.1160/th04-02-0135
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD40 antibodies in antiphospholipid syndrome and systemic lupus erythematosus

Abstract: Anti-beta2glycoprotein I (anti-beta2GPI) antibodies constitute the main autoantibody specificity in the sera of patients with antiphospholipid syndrome (APS). There is evidence that anti-beta2GPI antibodies induce the precoagulant activity of the endothelium by cross-linking the beta2 glycoprotein I (beta2GPI) on the cell surface. Since beta2GPI lacks intracellular domains, homology with other molecules such as CD40 that could initiate signaling, was extensively searched. A 86% homology between the amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Because of the lack of CD40 expression in both wild-type HEK293 and HEK293T4 cell lines, we can completely exclude the cross-reactivity between anti-␤ 2 GPI peptide Abs and CD40. [39][40][41] Furthermore, the phosphorylation of IRAK1, an adaptor protein involved in TLR signaling pathways, confirmed the specific TLR4 activation induced by anti-␤ 2 GPI peptide Abs in endothelial cells and monocytes. 39,[41][42][43] A previous study demonstrated the cross-reactivity between a subset of anti-transglutaminase Abs, typical serologic markers in patients with active celiac disease, with an epitope of the extracellular region of human TLR4 (aa 435-446).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Because of the lack of CD40 expression in both wild-type HEK293 and HEK293T4 cell lines, we can completely exclude the cross-reactivity between anti-␤ 2 GPI peptide Abs and CD40. [39][40][41] Furthermore, the phosphorylation of IRAK1, an adaptor protein involved in TLR signaling pathways, confirmed the specific TLR4 activation induced by anti-␤ 2 GPI peptide Abs in endothelial cells and monocytes. 39,[41][42][43] A previous study demonstrated the cross-reactivity between a subset of anti-transglutaminase Abs, typical serologic markers in patients with active celiac disease, with an epitope of the extracellular region of human TLR4 (aa 435-446).…”
Section: Discussionmentioning
confidence: 60%
“…39 The investigators suggested that Abs binding this peptide could react and potentially activate different cells expressing CD40 molecules on their surface. Nevertheless, our confocal microscopy experiments clearly demonstrated the specific binding of anti-␤ 2 GPI peptide Abs to TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Vlachoyiannopoulos et al . 15 identified a consensus motif between CD40 and p3 capable of interacting with aPLA. Although this sequence had one additional nonpolar amino acid between the polar and phenylalanine (ϕxFfζζϕϕϕ) amino acids, it was strongly related to the initial motif ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…21 Another research group highlighted a sequence homology between residues 239–245 of CD40 and residues 26–32 of β2GP1. 15 Residues 26–32 of β2GP1 corresponded to p3 and belonged to the ϕϕϕζζ part of the ϕϕϕζζϕFxϕ motif ( Figure 3 and Figure 5 ). Moreover, the hexapeptide TLRVYK, described by Blank et al .…”
Section: Discussionmentioning
confidence: 99%
“…33 Briefly, polystyrene microtiter plates were coated overnight with 50 L of recombinant ␤2GPI (10 g/mL). The plates were washed, blocked, and washed again as described before.…”
Section: Study Of Antigenicity Of ␤2gpi-pf4 Complexmentioning
confidence: 99%